KONTRIBUSI BURUH WANITA PENYADAP KARET TERHADAP PENDAPATAN KELUARGA (Studi Kasus di PTPN IX Kebun Balong/Beji-Kalitelo Afdelling Ngandong Kabupaten Jepara) - Malihatin Munawaroh; Sri Wahyuningsih; Shofia Nur Awami (MEDIAGRO, 2013)
The rapid population growth in rural areas led to increasing competition in obtaining employment. While on one hand meet the life needs in general and families in particular is increasing. This situation encourages women to entry for work as a rubber tapper in PTPN IX Balong Garden Beji Kalitelo. In this conditions women's tasks become increasingly a heavy that women have a three fold responsibility, in addition to acting as a housewife and social also act as a earner families. Study aims: 1) to know the allocation of time devoted women as breadwinners, take a rest, housewives and socially; 2) to know the factors that affect women's earnings rubber plantation workers; 3) to know how much the contribution of women rubber plantation workers of family income. Totally there are 80 samples of 565 population. The method which is used in this research is descriptive analysis method and an encode for processing use regression bifilar method. The results showed that the allocation of time to a living searching is the biggest allocation that is 9 hours a day with a percentage of 37,5 percent compared to other activities. Based on regression analysis revealed that work period factors, the results of rubber tapping and years of planting, significantly affect women's rubber tappers labor income. And an average contribution of women workers of the rubber tapper to the family income is 54,25 percent. Keywords: Contribution, family income, women workers.